2022
DOI: 10.3390/aerospace9100619
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Unsteady Shock Wave/Vortex/Turbulent Boundary Layer Interactions of a Hypersonic Vehicle during Its Shroud Separation

Abstract: Hypersonic vehicles are drawing more and more attention now and for the near future, especially in the low-altitudes near space, from 20 km to 45 km. The reliable separation of the protecting shroud from the hypersonic vehicle is a prerequisite and critical issue for the success of the entire flight mission. The unsteady multi-body separation characteristics and flow characteristics of hypersonic shroud separation at Mach 7.0 are investigated based on numerical simulation in this paper. The improved delayed de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In the development process of FlowStar software, a large number of standard models and engineering actual shape assessment and calibration have been carried out. Figure 4 gives out FlowStar soft thing to AIAA (Aircraft Industries Association of America) the fifth calculation flow of strength resistance prediction work conference [10] and AIAA second high The official statistical results of the lift prediction working conference [11] showed that the FlowStar software performed very well, and the results were near the statistical average of all the results of the conference, which was comparable to the well-known international CFD software in the industry [12]. (1) Strong shear layer.…”
Section: Validation Of Numerical Methodsmentioning
confidence: 62%
“…In the development process of FlowStar software, a large number of standard models and engineering actual shape assessment and calibration have been carried out. Figure 4 gives out FlowStar soft thing to AIAA (Aircraft Industries Association of America) the fifth calculation flow of strength resistance prediction work conference [10] and AIAA second high The official statistical results of the lift prediction working conference [11] showed that the FlowStar software performed very well, and the results were near the statistical average of all the results of the conference, which was comparable to the well-known international CFD software in the industry [12]. (1) Strong shear layer.…”
Section: Validation Of Numerical Methodsmentioning
confidence: 62%